Outcomes of Lumbopelvic Fixation in the Treatment of Complex Sacral Fractures Using Minimally Invasive Surgical Techniques. Issue 1 (April 2016) - Jazini, Ehsan; Nwodim, Emeka; Tannous, Oliver; Banagan, Kelley; Koh, Eugene; Ludwig, Steven; Gelb, Daniel
Introduction: Complex sacral fractures with vertical and anterior pelvic ring instability treated with traditional fixation methods are associated with high rates of failure and poor clinical outcomes. Supplemental lumbopelvic fixation(LPF) has been utilized for additional stability to help with fracture union. The purpose of this study was to determine if minimally invasive LPF provides reliable fracture stability and acceptable complication rates in complex sacral fractures. Methods: Twenty-eight patients were retrospectively chosen from a pool of 105 at our level 1 trauma center (2008–2014) who had undergone LPF. Patients underwent posterior sacroiliac fixation, with or without anterior fixation, followed by minimally invasive LPF. Main outcomes were return to the operating room (OR) for instrumentation revision secondary to loss of correction or failure of fixation, return to the OR for treatment of infection, radiographic evaluation to assess for loss of reduction. ISS score, transfusion requirements, length of hospital stay, postoperative day at mobilization, and mortality were also evaluated. Results: Three patients returned to the OR for infection (11%). One patient required revision surgery for instrumentation malposition and neurologic deficit (3.5%). No patients required return to the OR for revision due to failure of instrumentation or loss of correction. The average length of surgery was 3.9 hours and estimated blood loss was 192 mL. The average transfusion requirement was 2.2 units of packed red blood cells and the majority of patients were mobilized at postoperative day 4. There were no mortalities. Conclusion: This is currently the largest series of high energy complex sacral fractures treated with minimally invasive LPF. The results demonstrate reliable maintenance of reduction with a low complication rate.